The two-body collision controlled by the magnetic field and laser field near magnetic Feshbach resonance - Lyu, Bing-Kuan; Si, Bo-Wen; Yu, Zong-Han; Wang, Gao-Ren; Cong, Shu-Lin (Frontiers in Physics, 2023)
It is crucial to control the collision between ultracold atoms by applying external fields. We develop a theoretical model for investigating the s-wave scattering of ultracold atoms controlled by magnetic field and laser field. The calculation is performed by using the close-coupling method and mapped Fourier grid method. Due to the interference between the photoassociation and bound-to-bound transitions, the bound state in the continuum, which is a resonance with vanishing width, occurs at the magnetic field position near the magnetic Feshbach resonance. The widths of resonances in the neighborhood of the bound state in the continuum are narrow. Changing laser intensity can shift the magnetic field position where the bound state in the continuum occurs through modifying the ground molecular state, so as to induce wide resonances at desired magnetic field positions. By increasing the resonance width, the tunability of the real part of the scattering length at resonances can be significantly improved. Changing laser intensity can also adjust the coupling between the ground and excited molecular states. When the coupling between the ground and excited molecular states approaches zero, a resonance is induced, and the photoassociation and bound-to-bound transitions are both significantly suppressed at this resonance. Therefore, the atomic loss peak due to spontaneous emission does not appear at this resonance. The magnetic field position of this resonance is stable against the change in laser frequency.